2006
DOI: 10.1007/s00018-006-6095-6
|View full text |Cite
|
Sign up to set email alerts
|

The Foxa family of transcription factors in development and metabolism

Abstract: The Foxa subfamily of winged helix/forkhead box (Fox) transcription factors has been the subject of genetic and biochemical study for over 15 years. During this time its three members, Foxa1, Foxa2 and Foxa3, have been found to play important roles in multiple stages of mammalian life, beginning with early development, continuing during organogenesis, and finally in metabolism and homeostasis in the adult. Foxa2 is required for the formation of the node and notochord, and in its absence severe defects in gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
380
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(393 citation statements)
references
References 130 publications
11
380
1
1
Order By: Relevance
“…Foxa2 is a member of the Foxa subfamily of winged‐helix/ forkhead box (Fox) transcription factors comprised of three unlinked genes ( Foxa1, Foxa2, and Foxa3 ) that share a highly conserved DNA‐binding domain (Friedman & Kaestner, 2006). The structure of Foxa forkhead box has been solved and resembles that of H1 histone (Clark, Halay, Lai & Burley, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Foxa2 is a member of the Foxa subfamily of winged‐helix/ forkhead box (Fox) transcription factors comprised of three unlinked genes ( Foxa1, Foxa2, and Foxa3 ) that share a highly conserved DNA‐binding domain (Friedman & Kaestner, 2006). The structure of Foxa forkhead box has been solved and resembles that of H1 histone (Clark, Halay, Lai & Burley, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, members of the Foxa subfamily play important roles in early organ development and metabolism (24,25). We recently have shown that Forkhead box protein A3 (Foxa3), previously known to play a role in liver during long-term starvation and in pancreas development (26,27), is involved in the selective expansion of epididymal fat depots during a high-fat diet and in the suppression of energy expenditure during aging (28,29) and that its variants are associated with human metabolic traits (30).…”
mentioning
confidence: 99%
“…Because so many current mouse models display extreme phenotypes or embryonic lethality, and heterozygotes are usually unaffected, mutations in genes, especially null mutations, do not seem sufficient to explain NTDs (Bell et al, 2003;Bulgakov et al, 2004;Finnell et al, 2002;Friedman and Kaestrer, 2006;Hatakeyama et al, 2004;Hirata et al, 2001;Mathers, 2005;Nagai et al, 2000;Pierani et al, 2001;Sahara et al, 2007;Tachibana et al, 2002;Xu et al, 1999). miRNAs may offer a more subtle deregulation, and there is enough evidence that miRNA genes are under regulation by methylation to add plausibility to the idea (Bak et al, 2008;Han et al, 2007;Lujambio et al, 2007;Weber et al, 2007).…”
Section: Conclusion: Future Directionsmentioning
confidence: 99%